(untitled) (Global Journal of Human-Social Science, 2016)
This paper characterizes the use of spirals in rock carvings and other artifacts by early mankind. It formulates the hypothesis that these widely distributed symbols may represent chakras, which are typically considered the route for out-of-body experiences documented in some current vital energy disciplines. A characterization of the types of spirals commonly encountered in rock art, such as those found recently in a cave in Sardinia modelled on the Earth Goddess Gaia, and they suggested the hypothesis that Fermat spirals might also symbolize twoway communication.